Pendalaman Hubungan Strategis Cina di Myanmar Pasca Kudeta Militer Melalui Analisis Economic Statecraft - Aspin Nur Arifin; Hidayani, Fadhillah (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2025)
This study investigates China's strategic economic engagement with Myanmar after the 2021 military coup, focusing on the deployment of economic statecraft through the Belt and Road Initiative (BRI). The objective is to understand how China's pragmatic approach in foreign economic policy supports its geopolitical interests while consolidating influence in Southeast Asia. A qualitative research method with a case study approach was adopted. Data were collected through document analysis, including official reports, academic literature, and international databases, analyzed using the theoretical framework of economic statecraft to reveal patterns of strategic behavior. Findings show that China has sustained and expanded its economic activities in Myanmar post-coup, maintaining close ties with the military regime through state-owned enterprises (SOEs). Projects like the China-Myanmar Economic Corridor (CMEC), deep-sea ports, rail infrastructure, and mining operations have bolstered China’s strategic access to the Indian Ocean while insulating its interests from Western sanctions. The study reveals China's deliberate orchestration of commercial and diplomatic instruments to align Myanmar’s economic dependency with its broader geopolitical vision, particularly reducing reliance on the Malacca Strait and securing energy routes. China’s use of economic statecraft in Myanmar illustrates a proactive and calculated foreign policy strategy. Through infrastructure diplomacy and the mobilization of SOEs, China secures regional influence while advancing BRI goals. This study contributes to understanding power projection through economic instruments and suggests further research on comparative cases across the Global South.